The analysis and forecasting of coke prices - Papież, Monika; Śmiech, Sławomir (Analiza i prognozowanie cen koksu, 2011)
The authors of the paper, on the basis of data from the period 2003-2010, attempted to establish whether there is a link between coke prices and the prices of other resources. Since coke is one of the basic ingredients used in the process of steel production, its price should be correlated with coking coal price and the situation on the iron and steel markets. This situation is closely linked with the pace of world economy growth. It should be noted that the specificity of coke lies in the fact that its price is not quoted on world stock exchanges (like e.g. gold or petroleum). The article also presents the forecast of coke prices and the evaluation of the usefulness of the models used in forecasting.
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2011; Nr 196, s. 205-213
Keywords: prognozowanie; analiza cen; surowce energetyczne; prognozowanie cen; forecasting; price analysis; energy raw materials; prediction of prices